Chlorogenic acid supplementation during in vitro maturation improves maturation, fertilization and developmental competence of porcine oocytes. (28th June 2017) - Nguyen, T‐V; Tanihara, F; Do, LTK; Sato, Y; Taniguchi, M; Takagi, M; Van Nguyen, T; Otoi, T
Contents: Chlorogenic acid (CGA) is a quinic acid conjugate of caffeic acid, and a phytochemical found in many fruits and beverages that acts as an antioxidant. The present study investigated the effects of CGA supplementation during in vitro maturation (IVM), on in vitro development of porcine oocytes, to improve the porcine in vitro production (IVP) system. Oocytes were matured either without (control) or with CGA (10, 50, 100 and 200 μM). Subsequently, the matured oocytes were fertilized and cultured in vitro for 7 day. The rates of maturation, fertilization and blastocyst formation of oocytes matured with 50 μM CGA were significantly ( p  < .05) higher than those of the control oocytes. Hydrogen peroxide (H2 O2 ) is one of the reactive oxygen species and induces DNA damage in porcine oocytes. When oocytes were matured with 1 mM H2 O2 to assess the protective effect of CGA, 50 μM CGA supplementation improved the maturation rate and the proportion of DNA‐fragmented nuclei in oocytes compared with control oocytes matured without CGA. Moreover, when oocytes were matured with either 50 μM CGA (control) or caffeic acid (10, 50 and 100 μM), the rates of maturation, fertilization and the blastocyst formation of oocytes matured with 50 μM CGA were similar to those of oocytes matured with 10 and 50 μM caffeic acid. Our results suggest that CGA has comparable effects to caffeic acid, and IVM with 50 μM CGA is particularly beneficial to IVP of porcine embryos and protects oocytes from DNA damage induced by oxidative stress. Supplementation of CGA to the maturation medium has a potential to improve porcine IVP system.